Turkish medical educators’ TPACK components and characters: an analysis within the framework of simulation-based medical education - Karadag, Engin (BMC medical education, 2019)
Background Nowadays, a comprehensive approach is needed to describe the current status of the technology integration process and the identification of the factors that affect it, because the description and frame of the existing situation will be the starting point in the organization of the roadmap to the realization of an effective integration process. The purpose of this study is to identify the differences in technology integration of the medical educators working in Turkey and analyze these according to various variables on the basis of technological pedagogical content knowledge. Method Data used in the study were collected from 301 medical educators using the TPACK-Practical Scale and Attitude towards Technology Scale. The data were analyzed using Ward’s minimum variance hierarchical clustering analysis, discriminant function analysis and multinomial logistic regression analysis. Results According to the results of the study, medical educators’ technology integration was grouped in the following clusters, according to their TPACK: ( i ) activity-based, ( ii ) student- based and ( iii ) topic-based . It was found that the developed model explains 79 % of the variance of technology integration. The implementation of simulation-based medical education in medical school and the department where they work affect the clusters to which the medical educators were assigned, whereas the gender variable didn’t have an effect. The findings showed that attitudes towards technology, simulation education and working in the field of basic medical sciences increased medical educators’ activity-based presence. Conclusions The review of the clusters and their characteristics showed that there are similarities between the items used in the designing stage of the education programs and the relationships of these items among them. Learner centered approaches are based on the assumption that students are located at the center of the program. In these designs, teaching mostly focuses on the learner, rather than program, learning or administrative body. Individuals and their identities are crucial.